Pendidikan Gaya Hidup: Membentuk Kebiasaan Positif di Kalangan Generasi Muda - Agustina, Cynthya; Azizah, Nur (Journal of Sustainable Education, 2024)
The aim of this research is to determine the important role of education in forming positive habits of the younger generation, especially regarding healthy and sustainable lifestyles. The method used is an analytical approach, the author examines the factors that influence the formation of positive habits and effective educational strategies that promote the desired lifestyle. A detailed literature review was used to strengthen the conceptual framework linking education, lifestyle, and practice. The practical impact of these results is also examined, emphasizing the importance of collaboration between sectors and the role of parents in supporting the formation of positive habits in the younger generation. Lifestyle education plays an important role in shaping a healthier and more sustainable future for future generations.